POWER ABUSE IN CHARLES DICKENS'S DAVID COPPERFIELD: A MARXIST APPROACH - ISNIATI , ISNIATI (2006)
Power abuse is one of the social problems in the society. It is happen because there are two social class namely upper classes and lower class. Power abuse can be used as subject in literary work because literary work is a picture of human life. One of the literary work that use power abuses as subject is David Copperfield. The author of David Copperfield is Charles Dickens, a famous author at Victorian era. Power abuse is also related to the oppression so that so that it can be analyze by using Marxist Approach. Marxist Approach is one of the literary, which based on economic and political theories or Karl Marx. Literary work is picture of human. It means that the society influences literary work in many aspects such as social aspects, economic aspects, political aspects, science and technological aspect, cultural aspects, and religious aspects. In this novel, power abuse can be seen from characters and characterization, plot, style, and theme. This novel also analyzed based on Marxist approach. Dialectical materialism can be seen from characters and characterization, and plot. Historical materialism can be seen from character and characterization, plot, style, and theme. Alienation can be seen from character and characterization, plot, and setting. Revolution can be seen from character and characterization, and setting. Class struggle can be seen from character and characterization and plot. Revolution can be seen from character and characterization, setting, and plot. In this novel, power abuse is portrayed in many aspects such as social aspects, economic aspects, and politic aspects. In social aspects, power abuse can be seen from character and characterization, plot, style, and theme. In economic aspects, power abuse can be seen from character and characterization, plot, and theme. In politic aspects, power abuse can be seen from character and characterization.